Patient-controlled Analgesia with Target-controlled Infusion of Hydromorphone in Postoperative Pain Therapy. (January 2016) - Jeleazcov, Christian; Ihmsen, Harald; Saari, Teijo I.; Rohde, Doris; Mell, Jan; Fröhlich, Katharina; Krajinovic, Ljubica; Fechner, Jörg; Schwilden, Helmut; Schüttler, Jürgen
Abstract : Background: Patient-controlled analgesia (PCA) is a common method for postoperative pain therapy, but it is characterized by large variation of plasma concentrations. PCA with target-controlled infusion (TCI-PCA) may be an alternative. In a previous analysis, the authors developed a pharmacokinetic model for hydromorphone. In this secondary analysis, the authors investigated the feasibility and efficacy of TCI-PCA for postoperative pain therapy with hydromorphone. Methods: Fifty adult patients undergoing cardiac surgery were enrolled in this study. Postoperatively, hydromorphone was applied intravenously during three sequential periods: (1) as TCI with plasma target concentrations of 1 to 2 ng/ml until extubation; (2) as TCI-PCA with plasma target concentrations between 0.8 and 10 ng/ml during the following 6 to 8 h; and (3) thereafter as PCA with a bolus dose of 0.2 mg until the next morning. During TCI-PCA, pain was regularly assessed using the 11-point numerical rating scale (NRS). A pharmacokinetic/pharmacodynamic model was developed using ordinal logistic regression based on measured plasma concentrations. Results: Data of 43 patients aged 40 to 81 yr were analyzed. The hydromorphone dose during TCI-PCA was 0.26 mg/h (0.07 to 0.93 mg/h). The maximum plasma target concentration during TCI-PCA was 2.3 ng/ml (0.9 to 7.0 ng/ml). The NRS score under deep inspiration was less than 5 in 83% of the ratings. Nausea was present in 30%, vomiting in 9%, and respiratory insufficiency in 5% of the patients. The EC50 of hydromorphone for NRS of 4 or less was 4.1 ng/ml (0.6 to 12.8 ng/ml). Conclusion: TCI-PCA with hydromorphone offered satisfactory postoperative pain therapy with moderate side effects. Abstract : Using hydromorphone-specific pharmacokinetic parameters, accurate target-controlled infusions can be delivered. Using combined target-controlled infusion with patient-controlled analgesia, satisfactory postoperative pain control can be delivered with moderate levels of opioid-related side effects.Supplemental Digital Content is available in the text.